HUBUNGAN PIJAT OKSITOSIN TERHADAP KELANCARAN PRODUKSI ASI IBU POST PARTUM - Tuti Meihartati (Universitas Aisyiyah Yogyakarta, 2017)
Abstract: The purpose of this study was to determine the relationship between massage breast milk production smoothness of oxytocin on postpartum mother in BPM Ema Triana, Tanah Bumbu district. This type of research is analytic survey with cross sectional approach. Number of samples of post partum mothers in this study was 36. The sampling technique used is Non Probability. Technical analysis using chi-square test with 0.05. Analysis Chi-Square test results obtained significant correlation between oxytocin massage (P = 0.001) with the breast milk production smoothness post partum. The conclusion from this study is there is a relationship between oxytocin massage on postpartum breast milk production. Keywords: massage oxytocin, breast milk production, post-partum